Rezolvati sistemul:
-1x+1y-1=0
-2x+y-3=0
fdilcuoyna7n:
Prin ce metoda?
Răspunsuri la întrebare
Răspuns de
0
(1) -x+y=1
(2) -2x+y=3
(2) -(1) => -2x+y+x-y=3-1
-x = 2
x = -2
-2+y=1 => y=1+2 =3
(2) -2x+y=3
(2) -(1) => -2x+y+x-y=3-1
-x = 2
x = -2
-2+y=1 => y=1+2 =3
Răspuns de
0
- 1x + 1y - 1 = 0
- 2x + y - 3 = 0
- x + y = 1 | * (- 1)
- 2x + y = 3
x - y = - 1
- 2x + y = 3
- x = 2
x = 2
- 1 * 2 + y = 1
y = 1 + 2
y = 3
- 2x + y - 3 = 0
- x + y = 1 | * (- 1)
- 2x + y = 3
x - y = - 1
- 2x + y = 3
- x = 2
x = 2
- 1 * 2 + y = 1
y = 1 + 2
y = 3
Alte întrebări interesante
Chimie,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă